2021
DOI: 10.2174/1874847302109010009
|View full text |Cite
|
Sign up to set email alerts
|

Drying Potential of Leaves Oil of Zanthoxylum armatum DC from North India

Abstract: Background: The study on drying and its social acceptance has increased rapidly. Among different drying techniques, shade drying is one of the most feasible methods to keep intact from the decay of the main active components of the plant materials. Shade drying is an ancient drying method that increases durability, major constituents and activity of the plant material. Aims: Research was conducted to examine the drying potential of aromatic leaves oil of Zanthoxylum armatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Different studies using essential oils have identified linalool [15][16][17], α-pinene [10], 2undecanone [18][19][20], bornyl acetate [21], 3-borneol [12], β-terpinene [11], (Z)-β-ocimene [6], β-phellandrene [22], and 1,8-cineole [14] as major constituents. Numerous studies on the chemical makeup of Z. armatum essential oil have been published from different parts of India, such as Uttarakhand, Himachal Pradesh, Uttar Pradesh, etc., predominantly from Uttarakhand [6,10,16,19,21,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies using essential oils have identified linalool [15][16][17], α-pinene [10], 2undecanone [18][19][20], bornyl acetate [21], 3-borneol [12], β-terpinene [11], (Z)-β-ocimene [6], β-phellandrene [22], and 1,8-cineole [14] as major constituents. Numerous studies on the chemical makeup of Z. armatum essential oil have been published from different parts of India, such as Uttarakhand, Himachal Pradesh, Uttar Pradesh, etc., predominantly from Uttarakhand [6,10,16,19,21,23,24].…”
Section: Introductionmentioning
confidence: 99%